Pendekatan Terpadu dalam Teknik Peningkatan Kesuburan Tanah untuk Pertanian Berkelanjutan - Dama, Olis; Nurmi (Program Studi Agroteknologi INSTIPER, 2025)
Soil fertility is a key foundation for supporting the productivity and sustainability of agricultural systems, particularly amidst the challenges of land degradation and climate change. This study aims to comprehensively examine various techniques for improving soil fertility within a sustainable agriculture framework. The study employed a qualitative, descriptive approach using library research, through the search and analysis of various scientific journals, agronomy books, and research reports related to soil management. Data analysis was conducted using content analysis techniques, including data reduction, thematic classification, presentation, and comparative synthesis. The study identified five key techniques effective in improving soil quality: the use of organic fertilizers, soil liming, crop rotation and diversification, the utilization of soil microorganisms, and the application of biochar. Overall, each technique significantly contributed to improving the physical, chemical, and biological properties of the soil, increasing nutrient efficiency, and strengthening agroecosystem resilience. The comparative analysis demonstrated that the integration of these five techniques has the potential to produce a more holistic and adaptive soil management system suited to tropical agricultural conditions, particularly in Indonesia. This integrated approach is a crucial strategy for supporting long-term food security and environmental sustainability.